Nghiên cứu lí thuyết cơ chế phản ứng của axit fulminic với nguyên tử flo - Nghĩa, Nguyễn Trọng; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The mechanism for the HCNO + F reaction has been investigated at the B3LYP/6-311++G(3df,2p) level of theory. The potential energy surface (PES) for this system shows that there are ten different product pathways: PR1 (CNO· +HF), PR2 (HCN + OF·), PR3 (HCF: + NO), PR4 (OCNF + H), PR5 (FCN + ·OH), PR6 (HF + ·CNO_cy), PR7 (FCNO + H), PR8 (OCNH + F). PR9 (OCN· + HF) and PR10 (CO + NHF·). The results indicate that PR1 (CNO· +HF), PR3 (HCF: + NO) and PR5 (FCN + OH) are the major product channels with minor contributions from PR4 (OCNF + H), PR6 (HF + ·CNO_cy), PR8 (OCNH + F), PR9 (OCN· + HF), PR10 (CO + NHF·) whereas the other channels for PR2 (HCN + OF·), PR7 (FCNO + H) are less favorable. Keywords: Reaction mechanism, F atom, forming HF, fulminic acid HCNO, potential energy surface (PES).